The Death Penalty for Corruptors in Indonesia: Perspectives of Islamic Law and Positive Law: Opportunities and Challenges - Intan Nur Hidayah; Putri Majidah; Amelya Widyanti; Mekha Br. Sitepu; Naufal Rafi Shiddiq (ISNU Sumatera Utara, 2024)
This study examines the discourse on the death penalty for perpetrators of corruption in Indonesia from the perspective of Islamic law and positive law. In Islamic law, serious corruption can be categorized as a fasād fī al-ardḍ which allows for the imposition of the death penalty. Meanwhile, in Indonesian positive law, Article 2 paragraph (2) of the Corruption Eradication Law opens up normative space for the application of the death penalty in certain circumstances. This study also examines the opportunities and challenges of implementing this policy amidst pressure from human rights, political, and judicial systems. The results of the study indicate that normatively and sociologically, the death penalty is worthy of consideration in cases of serious corruption, although its implementation requires caution and legal reform.